Development of cloud services for patient-specific simulations of blood flows through aortic valves. (January 2017) - Kačeniauskas, A.; Pacevič, R.; Starikovičius, V.; Maknickas, A.; Staškūnienė, M.; Davidavičius, G.
Abstract: The paper presents the development of cloud software services for patient-specific computational analysis of blood flows through the aortic valve on a private university cloud. The main focus is on the software service level at the top of the provided computational platform. Blood flow through the aortic valve was considered as a pilot application of the OpenStack cloud infrastructure. A modelling software environment based on ANSYS Fluent was developed as a software service (SaaS) for the numerical analysis of low flow, low pressure gradient aortic stenosis. Segmentation software services were designed to deal with the patient-specific issues of the computational analysis. User-friendly management tools were developed using Apache jclouds API to enhance the management of OpenStack cloud infrastructure and to increase the accessibility of the required software. The performance of the cloud infrastructure was assessed by testing CPU, memory bandwidth, disk I/O and the developed software service for medical computations. The performance measured on Xen hardware virtual machines, KVM virtual machines and Docker containers were compared with the performance obtained by using the native hardware.